Embedding best transfusion practice and blood management in neonatal intensive care. Issue 1 (7th January 2020) - Flores, Cindy J; Lakkundi, Anil; McIntosh, Joanne; Freeman, Peter; Thomson, Amanda; Saxon, Ben; Parsons, Justine; Spigiel, Tracey; Milton, Sarah; Ross, Bryony
Abstract : Background: Transfusion is a common procedure for neonates receiving intensive care management. Recognising a paucity of patient blood management (PBM) programmes in neonates, we aimed to embed blood management and best transfusion principles in the neonatal intensive care unit (NICU) by aligning local policies, providing targeted education and partnering with parents. Methods: Practice-based evidence for clinical practice improvement (PBE-CPI) methodology was used. Previous hospital accreditation audits were reviewed and a neonate-specific transfusion audit was developed. Audit was performed at baseline and repeated following the intervention period. NICU clinicians received targeted education in obtaining informed consent, prescription and safe administration of blood components during a 'Blood Month' awareness period. A neonate-specific parent handout about transfusion was developed in partnership with parents. A pilot video demonstrating a shared consent discussion was also developed to assist in the consent process. Parents' knowledge, concerns and feedback regarding transfusion practice was sought at baseline (survey) and on project completion (experience trackers). Results: Neonate-specific baseline transfusion audit showed inconsistent consent, monitoring and documentation processes in neonatal transfusions. Post-targeted education audit showed improvement in these parameters. The targeted PBM and transfusion-related education delivered during 'Blood Month' was well-received by staff. Parents' feedback about the NICU transfusion consenting process was consistently positive. NICU medical and nursing clinicians (n=25) surveyed agreed that the parent handout was well set out, easy to understand and recommended that it be used to complement practice. Conclusion: PBE-CPI tools aligned with Australian PBM guidelines for clinicians and parents were well-accepted by clinical stakeholders and were associated with practice improvement in PBM awareness and transfusion consent processes. This PBE-CPI project developed NICU-specific consent information, not previously available, by partnering with parents to ensure quality of care in transfusion practice. Adoption of this also helps to meet accreditation for Australian Blood Management Standards. These strategies and tools translate readily into other NICUs to embed and support best PBM and transfusion practice.